Design and development of an impact breakage tester for rough rice - Afsar, A. K. M. Nurul; Jindal, Vinod Kumar; Singh, Gajendra; Koike, Masayuki; Kim, Kong-Hwan; The Royal Belgian Government (Bangkok : Asian Institute of Technology, 1982)
A centrifugal impact breakage tester was designed and fabricated for evaluating the milling potential of rough rice. The impact surface consisted of spring steel flat bars forming a cylinder which surrounded a rotating impeller. The test sample was introduced into the impeller through a hopper at a constant feed rate. The impeller rotated in a horizontal plane and threw the grains against the impact surface due to centrifugal action. Strain gages mounted on four individual cantilever bars were used to detect the impacts force in terms of a DC mv signal. The experimental impact breakage tester was used to measure the breakage susceptibility of rough rice. The output reading (DC mv) of the tester appeared to be linearly related with the percent breakage. The percent breakage was not influenced by the feed rate in the range of experimental values and it increased linearly with impeller rotation speed at any given moisture content. The percent breakage obtained in centrifugal tester had direct relationship with the specific rate of breakage in hammer mill tester and impact strength index in the drop test, In addition, all breakage results showed strong correlation with the laboratory milling yield, A relative comparison of different breakage tests revealed that the centrifugal tester was less sensitive to reflect the effects of drying treatment incomparison with the other two tests, However, it enabled faster testing of rough rice for milling potential assessment. The results of this study also showed that percentage breakage is a better indication of milling potential than DC mv reading in view of the practical difficulties encountered in the instrumentation of such a device.
A thesis submitted in partial fulfilment of the requirement for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1982
Keywords: Rice processing machines